THE EFFECT OF HYGIENE SANITATION AND PROMOTION ON PURCHASE DECISIONS AT FAVELA SUNSET CAFE BOGOR - Riani P. Ishak; Faisal Rabbania (JELAJAH: Journal of Tourism and Hospitality, 2022)
Cleanliness and sanitation are the most important things that must be considered to ensure that the products served to customers are safe and free from various viruses and bacteria. These issues, Hygiene Sanitation, and promotion must be considered by food and beverage entrepreneurs to increase the interest of buyers. The purpose of this study was to determine whether or not Hygiene Sanitation and Promotion influenced the purchase decisions at Favela Sunset Cafe Paledang, Bogor. The research method used is quantitative research. The data analysis used in this study consisted of multiple linear regression analysis with SPSS V 20.0. The result of the study concluded that the Effect of Hygiene Sanitation and Promotion on Purchase Decisions at Favela Sunset Cafe Paledang Bogor had a positive and significant influence.